ALASAN IBU HAMIL HIV POSITIF TIDAK MELANJUTKAN PERAWATAN PPIA KOMPREHENSIF DALAM ASPEK LAYANAN KESEHATAN - Suryanti, Putu Emy; Nerta, I Wayan (Institut Hindu Dharma Negeri Denpasar, 2020)
Prevention of mother to child transmission (PMTCT)is a government program aimed at preventing mother-to-child transmission of HIV.One of the comprehensive PMTCT program is HIV testing for all pregnant women and advanced therapy for all pregnant women whose test results are positive.The Government's target is 100% of HIV-positive pregnant women must be continuing the comprehensive PMTCT program, meanwhile there are HIV-positive pregnant women who discontinue the comprehensive PMTCT program.This study aims to explore the reasons of HIV-positive pregnant women to discontinue with the comprehensive PMTCT program. This study was a qualitative study through in-depth interviews with seven informants, namely : one HIV-positive pregnant woman whodiscontinue comprehensive PMTCT program, two HIV-positive women who gave birth the previous yearwhodiscontinue comprehensive PMTCT program, three public health centre (PHC) providers, and one head of PHC. Informants were selected using a purposive sampling technique. Data analysis was conducted thematically and the results were presented narratively to explore the reasons of HIV-positive pregnant women to discontinue with the comprehensive PMTCT program. Health care aspects of service readiness include the availability of PMTCT facilities and infrastructure, communication and attitudes of health providers in PMTCT program, waiting times for PMTCT program delivery, and assistance in PMTCT comprehensive program. Health care aspects of service readiness that are less than optimal can affect the understanding and desire of HIV-positive pregnant women to access comprehensive PMTCT program so that HIV-positive pregnant women discontinue comprehensive PMTCT program.